2017
DOI: 10.1017/s0031182017002244
|View full text |Cite
|
Sign up to set email alerts
|

The role of the mussel Mytilus spp. in the transmission of ostreid herpesvirus-1 microVar

Abstract: The Pacific oyster Crassostrea gigas contributes significantly to global aquaculture; however, C. gigas culture has been affected by ostreid herpesvirus-1 (OsHV-1) and variants. The dynamics of how the virus maintains itself at culture sites is unclear and the role of carriers, reservoirs or hosts is unknown. Both wild and cultured mussels Mytilus spp. (Mytilus edulis, Mytilus galloprovincialis and hybrids) are commonly found at C. gigas culture sites. The objective of this study was to investigate if Mytilus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In addition, a 14-fold OsHV-1 μVar replication was observed in mussels Mytilus spp. at 13 ℃ under experimental conditions [41]. The findings of this study would suggest that OsHV-1 μVar may be opportunistic, adapting to new circumstances, such as fewer available susceptible oysters due to the use of selectively bred oyster stocks more resistant to the virus, resulting in a "species jump" to another cohabiting bivalve species, and being transmissible at lower seawater temperatures.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, a 14-fold OsHV-1 μVar replication was observed in mussels Mytilus spp. at 13 ℃ under experimental conditions [41]. The findings of this study would suggest that OsHV-1 μVar may be opportunistic, adapting to new circumstances, such as fewer available susceptible oysters due to the use of selectively bred oyster stocks more resistant to the virus, resulting in a "species jump" to another cohabiting bivalve species, and being transmissible at lower seawater temperatures.…”
Section: Discussionmentioning
confidence: 83%
“…More recently OsHV-1 μVar was detected in different marine invertebrates including the Sydney cockle Anadara trapezia in Australia [39], in cultured Mytilus galloprovinciallis in Italy [40], in wild Mytilus spp. consisting of the blue Mytilus edulis, M. galloprovinciallis and hybrids of both parent species, in Ireland [41] and the green shore crab C. maenas [42]. Bookelaar et al [42] demonstrated that transmission of the virus could occur from C. maenas, previously exposed to the OsHV-1 μVar in the wild, to cohabiting naïve C. gigas within four days.…”
mentioning
confidence: 99%
“…OsHV-1 transmission to naive Pacific oysters has also been shown following cohabitation with exposed wild crabs (Carcinus maenas; Bookelaar et al, 2018) and mussels (Mytilus spp. ;O'Reilly et al, 2018). These taxa have previously been identified within vessel biofouling assemblages (Visscher, 1928;Apte et al, 2000;Moshchenko and Zvyagintsev, 2001;Coutts et al, 2003).…”
Section: Analysis Analysis Scopementioning
confidence: 86%
“…The ostreid herpesvirus OsHV-1 is lacking in host-specificity, meaning that it can also be found in scallops and clams including the invasive R. philippinarum (Ben-Horin et al, 2015), as is the microvariant which can be found in Mytilus spp. (O'Reilly et al, 2018) and C. maenas (Bookelaar et al, 2018), and this could further extend dispersal capability.…”
Section: Climate Change and Bivalve Diseases: Potential Outcomes For Parasite Transmissionmentioning
confidence: 98%